PARADOKS PERUBAHAN SOSIAL BALI DALAM CERPEN INDONESIA DAN BALI MODERN - Sujaya, I Made; Adhi Dwipayana, I Kadek; Liswahyuningsih, Ni Luh Gede (Program Studi Pendidikan Bahasa Indonesia dan Daerah Universitas PGRI Mahadewa Indonesia, 2024)
This article discusses the representation of Balinese social change in modern Indonesian and Balinese short stories. The objects of study are the Indonesian short story,